Inflammatory immune response and its key roles in the process of bone fractures healing - Abdel-Mageed, Ahmad M.; M. M, Abdellatif; Y. H, Ali; Intisar, Intisar K.S; Shahhat, Ismail M. A. M.; Abu-Tahon, Medhat Ahmed; Abdein, Mohamed A.; Aljameeli, Mohammad M.; Elsheikh, Salma Yousif Sidahmed; Elwasefy, Shereen Ahmed; et al. (Edelweiss Applied Science and Technology, 2024)
Bone fractures, which represent 2% - 5% of adults annually, are considered a significant health concern, particularly as their incidence has recently increased. Bones are composed of minerals such as calcium and phosphate, and organic components like type I collagen, provide structural integrity and strength. The periosteum plays a vital role in bone healing, with children’s thicker periosteum contributing to faster recovery compared to adults. This review emphasizes the critical role of the immune system in bone fracture healing, highlighting the inflammatory response as a key factor in bone healing. Immediately after the occurrence of a fracture, immune cells are recruited to the site of the fracture, initiating a cascade of healing processes that include angiogenesis and tissue repair scenarios. The healing process is classified into primary and secondary healing, each with distinct mechanisms. Factors influencing healing include fracture location, patient age, physical activity levels, medical conditions, medication use, smoking, and the biomechanical environment. The healing phases—inflammatory, repair, and remodeling—are regulated by the immune cells, particularly macrophages and T-cells, which can either facilitate or hinder recovery. Understanding the immune response is essential to developing effective therapeutic strategies for the healing of the bone structures.